Effectiveness of Service Quality through Integrated Information Systems in Increasing Customer Satisfaction and Loyalty in Islamic Education Institutions - Silwana Mumthaza; Eni Fariyatul Fahyuni; Yayuk Faujiyah (International Consortium of Education and Culture Research Studies, 2020)
In the management of Islamic Education Institutions based on management, efforts are needed to improve the quality of comprehensive human resources so that the quality of human beings in Indonesia can adapt well with the development of technology and times (Mutohar, 2014). Therefore Islamic Educational Institutions need a system that helps consumers get information. The information provided aims to provide better communication so that the program of Islamic Education institutions achieving educational goals will become smoother (Yukl, 2017). The implementation of this management concept has 3 key elements including customer satisfaction, service quality and customer loyalty (Kunaifi, 2016). In this case customer satisfaction with information obtained at the time of learning activities becomes importantThis satisfaction increases consumer loyalty at school. This study aims to provide an overview and information system that facilitates the public to receive better communication. This study also examines more deeply how information systems are able to provide satisfaction and increase loyalty to consumers of Islamic Education Institutions. This study uses qualitative data collection methods, namely research procedures that produce descriptive data in the form of information directly, in depth, unstructured. This research was conducted at SMA Muhammadiyah 2 Sidoarjo. Primary data sources were obtained from information in the form of interviews with related parties handling the Integrated Information System including the Deputy Principal for Student Affairs, Deputy Principal for Public Relations, IT team and Principal. Secondary data obtained from data that already exists and previous and has a relationship problem that is examined includes the existing literature. The population of the research sample was the guardians of students in SMA Muhammadiyah 2 Sidoarjo. Data collection techniques include interviews and Literature studies. Interviews were conducted with open-ended questions. Literature study is done by reading literature books, journals, internet and previous research that has been done before. From the analysis and results of the discussion obtained it can be concluded as follows: Integrated information systems have good benefits to schools so that schools can develop marketing and community trust as well-facilitated schools. The existence of an integrated information system can be an added value in increasing the satisfaction and loyalty of guardians of students, students and stakeholders who are interested in the school environment. Integrated information systems always experience developments in accordance with the technology that developed in that year. Therefore, competent funding and human resources are needed in managing the system.